Henrik Bergstrøm-Nielsen, Henrik Lange & Henry Verner Larsen; redaktionelle medarbejdere: Anton Andersen, Peter Jürgensen & Hans-Otto Rosenbohm: Dansk-tysk ordbog. København: Munksgaard, 1992 - Lauridsen, Ole (HERMES - Journal of Language and Communication in Business, 1993)
No abstract.